1992
DOI: 10.1111/j.1439-0434.1992.tb04315.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Indian Cassava Mosaic Virus

Abstract: The Indian cassava mosaic virus (ICMV) was transmitted by the whitefly Bemisia tahaci and sap inoculation. ICMV was purified from cassava and from systemically infected Nicotiana benthamiana leaves. Geminate particles of 16-18 X 30 nm in size were observed by electron microscopy. The particles contained a single major protein of an estimated molecular weight of 34,000. Specific antiserum trapped geminate particles from the extracts of infected cassava and N. benthamtana plants in ISEM test. The virus was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…The infected plant developed systemic symptoms of downward curling of the upper leaves 2-3 weeks after inoculation, resulting in slight stunting of the plant. These symptoms resemble those reported for an isolate of ICMV from southern India (Mathew and Muniyappa, 1992). The virus was also transmitted with low efficiency between N. benthamiana plants (3/100 inoculated plants over two experiments) to produce similar mild symptoms.…”
Section: Mechanical Transmission Of Icmv and Slcmv Isolatessupporting
confidence: 74%
“…The infected plant developed systemic symptoms of downward curling of the upper leaves 2-3 weeks after inoculation, resulting in slight stunting of the plant. These symptoms resemble those reported for an isolate of ICMV from southern India (Mathew and Muniyappa, 1992). The virus was also transmitted with low efficiency between N. benthamiana plants (3/100 inoculated plants over two experiments) to produce similar mild symptoms.…”
Section: Mechanical Transmission Of Icmv and Slcmv Isolatessupporting
confidence: 74%
“…From the study it could be observed that the molecular weight of the virus under study was estimated to be 35 kDa. This result is in agreement with the results obtained by Mathew and Muniyappa (1992), wherein the 34 kDa of coat protein of ICMV was reported. Harrison (1985) reported that the gemini virus particles consists of 80% protein, which typically is a single species of molecular weight of 27 -32 kDa; this study has also confirmed that the virus under investigation is the gemini virus.…”
supporting
confidence: 96%
“…BGYMV was purified according to the procedure given by Mathew and Muniyappa (1992). One hundred grams of leaves from the BGYMV-infected bitter gourd plants were harvested 18 days after inoculation and homogenized in 0.1 M sodium phosphate buffer pH 7.8 (2 ml/g) containing 1% 2-mercaptoethanol, 0.0001 M cysteine hydrochloride, 0.001 M sodium EDTA and chloroform (1 ml/g).…”
Section: Purification Of Bgymvmentioning
confidence: 99%
“…These viruses are African cassava mosaic virus (ACMV), East African cassava mosaic virus (EACMV), East African cassava mosaic Cameroon virus (EACMCV) (Fondong et al, 2000), East African cassava mosaic Kenya virus (EACMKV) (Bull et al, 2006), East African cassava mosaic Malawi virus (EACMMV) (Zhou, et al, 1998), East African cassava mosaic Zanzibar virus (EACMZV) (Maruthi et al, 2004) and South African cassava mosaic (SACMV) (Berrie et al, 1998). Two other viruses, Indian cassava mosaic virus (ICMV) (Matthew and Muniyappa, 1992;Saunders et al, 2002) and Sri Lankan cassava mosaic virus (SLCMV) (Saunders et al, 2002), were reported from the Indian sub-continent.…”
Section: Introductionmentioning
confidence: 99%